(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Thalassemia is a genetic blood disorder that can lead to significant splenic complications. Ultrasound assessment of the spleen in thalassemia patients is crucial for early detection and management of these complications. Objective: To sonographically assess spleen characteristics in patients with thalassemia. Methods: This prospective observational study included 101 thalassemia patients at Dastak hospital, Sabzazar, Lahore, over a 9-month period. Patients of all ages and genders with confirmed thalassemia diagnoses were included, while normal individuals, those with abdominal distension, and previous abdominal surgery were excluded. Ultrasound examinations were performed to assess spleen size, volume, and echogenicity. Results: The mean age of patients was 7.32 years, with 68.3% having thalassemia major and 31.7% thalassemia minor. The mean spleen size was 13.64 cm, and the mean volume was 83.92 cm³. Splenomegaly was observed in 65.3% of patients, with 74.3% showing hyperechoic spleens. A significant association was found between patient age and spleen abnormality (p = 0.036), as well as between thalassemia type and increased spleen echogenicity (p = 0.001). Conclusion: Ultrasound assessment revealed significant splenic changes in thalassemia patients, with associations between spleen characteristics, age, and thalassemia type. These findings emphasize the importance of regular sonographic monitoring of the spleen in thalassemia patients for guiding treatment and assessing disease progression.